Hukuman mandatori bagi pesalah dadah di Malaysia dan Republik Indonesia - Waluyaningsih, 1964- (Dewan Bahasa dan Pustaka, 1997)
Comparative study of Malaysian and Indonesian laws on drug abuse and punishment.